ANALISIS FORMULASI KEBIJAKAN PENDIDIKAN SELAMA MASA KRISIS PANDEMI COVID-19 DI KOTA JAMBI - Masruroh, Ina (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2024)
This study aims to analyze the educational relaxation policy formulation process during the Covid-19 crisis. Policies that appear during an emergency are certainly different from the policies available during normal times. This difference focuses on the minimal availability of information and the time pressure that is demanded faster than usual. This study uses John Kingdon's multiple stream theory to see the interactions that arise in policy formation during an emergency. The method used is qualitative research by adjusting the crisis situation during the Covid-19 pandemic. The results show that the educational relaxation policy process comes from the integration of the flow of problems, policies and politics that influence each other. These streams are integrated with each other because in practice in times of crisis, the position of policy actors is filled by the same actors at each stage of policy making. This study explains that conflicts of interest that occur in times of crisis can be minimized by inclusive coordination between affected and authorized regional institution. This coordination can be seen from the exchange of information and resources owned by each regional agency. Worries about the domino effect during the Covid-19 pandemic crisis have made policy actors voluntarily cooperate and help according to their respective capacities. The role of the mayor as regional head and the head of the Covid-19 task force is the most dominant position in setting policy. His great power is able to unite local institution who have different interests. Thus, this actor is identified as a policy entrepreneur in this policy. Keywords: Policy Formulation; Local Policy; Multiple Stream Approach.